2023
DOI: 10.1186/s12967-022-03870-1
|View full text |Cite
|
Sign up to set email alerts
|

D-Mannose prevents bone loss under weightlessness

Abstract: Background Astronauts undergo significant microgravity-induced bone loss during space missions, which has become one of the three major medical problems hindering human's long-term space flight. A risk-free and antiresorptive drug is urgently needed to prevent bone loss during space missions. D-mannose is a natural C-2 epimer of D-glucose and is abundant in cranberries. This study aimed to investigate the protective effects and potential mechanisms of D-mannose against bone loss under weightles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…It can also be used as a carbohydrate nutrient to participate in immunomodulation and anti-tumor functions. Mannose has been widely used in industries such as food, medicine, cosmetics, and food additives [44]. Ribose exists in the form of glycoside in cells and furanose in mycelium, which is involved in the synthesis of vitamins and coenzymes.…”
Section: Component Analysis Of Polysaccharidementioning
confidence: 99%
“…It can also be used as a carbohydrate nutrient to participate in immunomodulation and anti-tumor functions. Mannose has been widely used in industries such as food, medicine, cosmetics, and food additives [44]. Ribose exists in the form of glycoside in cells and furanose in mycelium, which is involved in the synthesis of vitamins and coenzymes.…”
Section: Component Analysis Of Polysaccharidementioning
confidence: 99%
“…As for bone loss, it was found that D-mannose attenuated bone loss induced by senility and estrogen de ciency in mice, which may be mediated by D-mannose-induced proliferation of Tregs and gut microbiota-dependent anti-in ammatory effects [18]. Another study showed that D-mannose protected against bone loss in rats under weightlessness, which was mediated by inhibiting osteoclast cell fusion [19]. However, whether D-mannose can alleviate periodontitis by regulating the functions of neutrophils remains unknown.…”
Section: Introductionmentioning
confidence: 99%